The detection of a population of submillimeter-bright, strongly lensed galaxies - Negrello, M; Hopwood, R; De Zotti, G; Cooray, A; Verma, A; Bock, J; Frayer, D; Gurwell, M; Omont, A; Neri, R; Dannerbauer, H; Leeuw, L; et al. (2010)
Gravitational lensing is a powerful astrophysical and cosmological probe and is particularly valuable at submillimeter wavelengths for the study of the statistical and individual properties of dusty star-forming galaxies. However, the identification of gravitational lenses is often time-intensive, involving the sifting of large volumes of imaging or spectroscopic data to find few candidates. We used early data from the Herschel Astrophysical Terahertz Large Area Survey to demonstrate that wide-area submillimeter surveys can simply and easily detect strong gravitational lensing events, with close to 100% efficiency.